Unr Is Required In Vivo for Efficient Initiation of Translation from the Internal Ribosome Entry Sites of both Rhinovirus and Poliovirus - Boussadia, Oréda (American Society for Microbiology, 2003)
Translation of picornavirus RNAs is mediated by internal ribosomal entry site (IRES) elements and requires both standard eukaryotic translation initiation factors (eIFs) and IRES-specific cellular trans-acting factors (ITAFs). Unr, a cytoplasmic RNA-binding protein that contains five cold-shock domains and is encoded by the gene upstream of N-ras, stimulates translation directed by the human rhinovirus (HRV) IRES in vitro. To examine the role of Unr in translation of picornavirus RNAs in vivo, we derived murine embryonic stem (ES) cells in which either one (−/+) or both (−/−) copies of the unr gene were disrupted by homologous recombination. The activity of picornaviral IRES elements was analyzed in unr(+/+), unr(+/−), and unr(−/−) cell lines. Translation directed by the HRV IRES was severely impaired in unr(−/−) cells, as was that directed by the poliovirus IRES, revealing a requirement for Unr not previously observed in vitro. Transient expression of Unr in unr(−/−) cells efficiently restored the HRV and poliovirus IRES activities. In contrast, the IRES elements of encephalomyocarditis virus and foot-and-mouth-disease virus are not Unr dependent. Thus, Unr is a specific regulator of HRV and poliovirus translation in vivo and may represent a cell-specific determinant limiting replication of these viruses.